2012
DOI: 10.4049/jimmunol.1101435
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin 4A Exerts a Proangiogenic Effect by Enhancing Vascular Endothelial Growth Factor-A Expression in Macrophages

Abstract: The axon guidance cues semaphorins (Semas) and their receptors plexins have been shown to regulate both physiological and pathological angiogenesis. Sema4A plays an important role in the immune system by inducing T cell activation, but to date, the role of Sema4A in regulating the function of macrophages during the angiogenic and inflammatory processes remains unclear. In this study, we show that macrophage activation by TLR ligands LPS and polyinosinic-polycytidylic acid induced a time-dependent increase of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 67 publications
1
67
0
Order By: Relevance
“…Indeed, whilst directly inhibiting physiological angiogenesis [172], Sema4A is highly expressed in macrophages activated by several inflammatory stimuli and recruited at the injured area in a cardiac ischaemia/reperfusion model. As a result, Sema4A activates a specialized genetic programme in macrophages that enhances VEGF-A production and promotes angiogenesis [173]. In addition, it has been reported that Sema3B indirectly enhances cancer metastasis by increasing the expression of interleukin-8 in cancer cells, which in turn increases the recruitment of TAMs that favour metastatic dissemination [174].…”
Section: Sema3 Signalling and Bmdcsmentioning
confidence: 99%
“…Indeed, whilst directly inhibiting physiological angiogenesis [172], Sema4A is highly expressed in macrophages activated by several inflammatory stimuli and recruited at the injured area in a cardiac ischaemia/reperfusion model. As a result, Sema4A activates a specialized genetic programme in macrophages that enhances VEGF-A production and promotes angiogenesis [173]. In addition, it has been reported that Sema3B indirectly enhances cancer metastasis by increasing the expression of interleukin-8 in cancer cells, which in turn increases the recruitment of TAMs that favour metastatic dissemination [174].…”
Section: Sema3 Signalling and Bmdcsmentioning
confidence: 99%
“…23 However, it was also found to produce an opposite effect and enhance angiogenesis by enhancing VEGF expression. 109 Unlike sema3E, sema4A also utilizes type-B plexins, 246,247 neuropilin-1 248 and Tim-2 83 as signal transducing receptors. Sema4A is a well characterized modulator of immune responses 229 and may also affect tumor progression via the immune system.…”
mentioning
confidence: 99%
“…Sema3E/Plexin-D1 interactions are also important during angiogenesis, principally through their action on endothelial cell migration (Kim et al, 2011; Oh and Gu, 2013). In this system, however, additional ligands for Plexin-D1 have been identified, including other secreted Sema3 ligands or the membrane-bound Sema4A (Bellon et al, 2010; Meda et al, 2012; Toyofuku et al, 2007). These ligands have been mapped in the mouse forebrain during development and, except for Sema3E, do not appear to be expressed in the developing cortex during early postnatal development (P0 – P21; Allen Brain Atlas, http://developingmouse.brain-map.org/).…”
Section: Discussionmentioning
confidence: 99%